MANAJEMEN MAJELIS TAKLIM DALAM MENINGKATKAN KEGIATAN KEAGAMAAN MAJELIS TAKLIM AL-HIDAYAH CILEDUG TANGERANG - Iksaniah Ardi, Zian; Asrof Fitri, Ahmad; Suryandari, Meity (Cahaya Ilmu Bangsa Institute, 2024)
With the advancement of technology that is developing rapidly, Al-Hidayah taklim assembly is quite far behind. Even so, it does not affect the local residents not to do activities at the Al-Hidayah taklim assembly. The community is still very enthusiastic about activities at the Al-Hidayah taklim assembly. This is a challenge for the management in managing the religious activities of the Al-Hidayah taklim assembly. This research analyzes the management of religious activities at Majelis Taklim Al- Hidayah. This research aims to analyze the management applied by the management of Majelis Taklim Al-Hidayah in an effort to improve religious activities. In addition, this study will find out what are the supporting and inhibiting factors of taklim assembly activities. To obtain data, researchers will conduct observations, interviews, and documentation. The main supporting factors in the management of activities include a strategic location that is easy to reach, sincere devotion from administrators who act as teachers, and awareness of the surrounding community of the importance of Islamic religious knowledge. However, the majelis taklim also faces challenges, especially limited operational funds, lack of competent human resources (HR), and low levels of technological literacy among the community. This is an obstacle in managing the activities of the majelis taklim. Keywords: management, taklim assembly, religious activities;